SAT0362 Incidence of Adverse Events in Patients with Rheumatoid Arthritis and Spondyloarthritis Exposed to Anti-Tnf Therapy. Data from the Brazilian Registry for Monitoring of Biologic Therapies in Rheumatic Diseases (Biobadabrasil). (9th June 2015) - Ranza, R.; Laurindo, I.; Titton, D.; Barbosa, L.; Bertolo, M.; Bertaccini, J.; Brenol, C.; Carvalho, H.; Castro, G.; Cecconi, M.; Costa, I.; Duarte, A.; et al.
Abstract : Background: The safety profile of a-TNF drugs might have regional differences due to socio economic factors and epidemiology of infectious diseases. In 2009, the Brazilian Society of Rheumatology started BiobadaBrasil registry, part of a Latin America project (BiobadaAmerica) with methodological support of SER and Biobadaser Objectives: To report the incidence of adverse events (AE) in patients exposed to a-TNF drugs in Brazil Methods: Since 2009, 31 centers from 21/26 states included patients with active rheumatic diseases starting a biologic drug or a synthetic DMARD (control group). A constant monitoring of data quality has been done (online, by phone and ïn situ"). This study focuses on serious AE (SAE) and serious infectious AE (SIAE) in patients with RA and SpA (AS and PsA) exposed to a-TNF.Time of exposure was set from start of the drug to the date of last administration plus twice the half-life. Continuous variables were expressed as mean (SD).AE incidence rate as 1000 p/y with 95%CI.Data 31/12/13 Results: 1483 subjects with RA (952) and SpA (531) exposed to a-TNF drugs were included in BiobadaBrasil, 3882 p/y, mean age 47 (12) yrs, mean dis dur 9 (8) yrs, 65% females. Controls were 529 (RA 491, SpA 38), 1607 p/y, mean age 50 (12) yrs, mean dis dur 6 (8) yrs, 82% females. The incidence rates of AE in the a-TNF vs control groups were: SAE 69 [61, 78] vs 30 [23, 40] (ratio 2.31 [1.7, 3.14] p=0.000), SIAE 35 [30, 41] vs 12 [8, 19] (ratio 2.96 [1.83, 4.79] p=0.000). First a-TNF was associated with lower incidence of SAE and SIAE when compared with the subsequent (SAE 66 vs 97, ratio 1.47 [1.05, 2.06], p=0.024) (SIAE 34 vs 44, ratio 1.22 [0.78, 2.10], p=0.3). SAE and SIAE were less frequent in SpA than in RA (SAE ratio 0.69 [0.52, 0.93], p=0.014) (SIAE ratio 0.53 [0.33, 0.83], p=0.006) Conclusions: In BiobadaBrasil registry, patients exposed to a-TNF drugs have incidence rates of SAE and SIAE respectively 2 and 3-fold those of the control group, significantly lower in SpA than in RA. Acknowledgements: BiobadaBrasil study group: P Cabral data quality control, BSR, A Kakehasi UFMG Belo Horizonte, A. Ximenes HGG, Goiania, F Sztajnbok UERJ Rio Janeiro, H. Pereira HUGV Manaus, I Silveira PUCRS Porto Alegre, A Ranzolin UFPE Recife, A Hayata CRO Osasco, M Abreu UFSC São Carlos, M Scheinberg HAS São Paulo, W Bianchi SCM Rio Janeiro, W Chahade HSPE São Paulo Disclosure of Interest: None declared